Biodegradation of starch films: The roles of molecular and crystalline structure. (20th May 2015) - Li, Ming; Witt, Torsten; Xie, Fengwei; Warren, Frederick J.; Halley, Peter J.; Gilbert, Robert G.
Highlights: The enzymatic degradation of starch films with varied structures is investigated. The molecular, crystalline and granular structures are varied using pre-treatments. Two degradation mechanisms are developed for the films with varied structures. Small starch molecules are more soluble and readily degradable by an enzyme. The retrograded structure inhibits enzymatic degradation. Abstract: The influences of molecular, crystalline and granular structures on the biodegradability of compression-molded starch films were investigated. Fungal α-amylase was used as model degradation agent. The substrates comprised varied starch structures obtained by different degrees of acid hydrolysis, different granular sizes using size fractionation, and different degrees of crystallinity by aging for different times (up to 14 days). Two stages are identified for unretrograded films by fitting degradation data using first-order kinetics. Starch films containing larger molecules were degraded faster, but the rate coefficient was independent of the granule size. Retrograded films were degraded much slower than unretrograded ones, with a similar rate coefficient to that in the second stage of unretrograded films. Although initially the smaller molecules or the easily accessible starch chains on the amorphous film surface were degraded faster, the more ordered structure (resistant starch) formed from retrogradation, either before or during enzymatic degradation, strongly inhibits film biodegradation.